(untitled) (Journal of Tropical Pharmacy and Chemistry, 2025)
This study aims to the antimicrobial activity test of leaf extract of B. virgata, and the Minimum Inhibitory Concentration values determine to​​ against some microbes with solid dilution method The materials in maceration with methanol were obtained with 500 grams, than partitioned with solid liquid partition method to use n-hexane, methanol-soluble extract obtained by n-hexane and methanol extracts insoluble n-hexane, both extracts was chemical component monitoring with Thin Layer Chromatography (TLC), then tested with solid dilution method its activity. Antimicrobial activity test results from both types of extracts, methanol extract soluble fraction of n-hexane showed better than activity methanol extract of insoluble fraction of n-hexane, because it can inhibit the growth of the bacteria E. coli, V. cholerae and S. thyposa, while the methanol extract of n-hexane insoluble only able to inhibit the bacteria V. cholerae, methanol-soluble extract fraction of n-hexane as the active extracts 1000 ug / ml medium that can kill or inhibit of microbes the growth.